Odpowiedzi

2009-10-08T13:54:41+02:00
(-3-6)*(5-1):8=[(-3)*4]:8=(-12):8=1,5

-3-(6*5)-1:8=-3-30-1:8=3-30-8=-3-3,75=-0,75
Najlepsza Odpowiedź!
2009-10-08T14:08:41+02:00
1) (-3-6)×5-1÷8=-9×5-1÷8=-45-1/8=-451/8
2) -3-(6×5-1)÷8=-3-29÷8=-3-3,625=-6,625
3)-3-6×(5-1)÷8=-3-6×4÷8=-3-24÷8=-3-3=-6
4)nawias kwadratowy-3-(6×5)-1zamknąć nawias kwadratowy÷8=
(-3-30-1)÷8=-34÷8=-4,25
2009-10-08T14:22:20+02:00
1) -3-(6×5-1)÷8=
=-3-29÷8=-3-3,625=-6,625

2) [-3-(6×5)-1]÷8=
(-3-30-1)÷8=-34÷8=-4,25

3)-3-6×(5-1)÷8=
-3-6×4÷8=-3-24÷8=-3-3=-6

4)(-3-6)×5-1÷8=-9×5-1÷8=-45-1/8=-451/8